ANALISIS YURIDIS TERHADAP PERATURAN PRAKTIK PERDAGANGAN MELALUI JASA TITIP BARANG IMPOR: Juridical Analysis Of The Practice Of Trade Through Import Goods Enstrument Services - Majah Sabrina; Sharda Abrianti (Faculty of Law, Universitas Trisakti, 2025)
The practice of entrusting imported goods is an activity in which individuals travel abroad to purchase goods at the request of consumers, then bring them back to Indonesia in exchange for services. This activity is rampant, but has not been strictly regulated in Indonesian regulations, resulting in a legal vacuum. The formulation of the problem in this research is whether trade through entrustment services is included in import activities that must fulfill customs requirements and applicable import regulations. This research uses descriptive normative juridical method with qualitative approach and deductive analysis technique. The data used consists of secondary data as the main source and primary data as a complement. The results and the conclusion showed that the services of entrusting imported goods are classified as legitimate service import activities as long as they fulfill the provisions in the Minister of Trade Regulation No. 7 of 2024. However, in practice, many entrusted service providers do not have a Business Identification Number as an Importer Identification Number, and disguise entrusted goods as personal belongings of passengers to avoid import duties and Taxes in the Framework of Import.